PENGARUH SOCIAL MEDIA MARKETING, BRAND AWARENESS, DAN ELECTRONIC WORD OF MOUTH TERHADAP NIAT BELI - Hilda aulia Hilda; Ajeng Aquinia (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
The research objective is to analyze the effect of Social Media Marketing, Brand Awareness, and Electronic Word of Mouth on Purchase Intentions. The research was conducted on consumers who use Samsung Smartphones. Consumers who use Samsung smartphones are determined to be the population of this study. The purposive sampling method was used as a sampling technique and a total of 100 respondents were obtained. Data were analyzed through reliability test with Cronbach alpha. validity test with KMO and Component Matrix, as well as multiple regression analysis. The results of the study found that "there is a significant positive influence on Social Media Marketing, and Electronic Word of Mouth on Purchase Intentions. Meanwhile, Brand Awareness has no effect on Purchase Intentions. Keywords : Social Media Marketing, Brand Awareness, Electronic Word of Mouth